Panel Data Analysis on Rice (Paddy) Production in Indonesia 2018-2021 : Panel Data Analysis on Rice (Paddy) Production in Indonesia 2018-2021 - Yohandoko , Setyo; Supriyanto, Supriyanto (International Journal of Mathematics, Statistics, and Computing, 2023)
Rice is the staple food of Indonesian society. Rice (Paddy) as a staple food for Indonesian people is an important commodity for the government in effort to maintain national food security. Food security can be fulfilled if a country has sovereignty over food. Food sovereignty can be realized if domestic production meet its people consumption needs. Therefore, this research pays attention to government policies in effort to increase rice (paddy) production optimally. The policies analyzed included the realization of subsidized fertilizer distribution, the realization of insurance for rice farming, the realization of activities for developing agricultural irrigation units, and farmer exchange rates. Analysis was performed using panel data regression. From this research, it can be concluded that the distribution of subsidized fertilizers, the development of agricultural irrigation units, and the availability of farmer financing in the agricultural financing index positively affect the increase in domestic rice production. Conversely, the occurrence of rice crop insurance claims indicates crop failure in a certain region. This disruption negatively impacts the quantity of domestic rice production. On the other hand, having agricultural insurance provides a guarantee of financing for farmers when they experience crop failure.